An investigation into teachers’ perceptions on the role of group work in the teaching of early childhood education learners in St Patrick’s cluster, Gweru district, Zimbabwe - Moyo, Sindiso (Midlands State University, 2018)
This research investigated teachers’ perceptions on the role of group work in the teaching of Early Childhood Education (ECE) learners in St. Patrick’s Cluster. An introduction to the study which presented the background to the study highlighted some researches that were carried out on group work. These included studies carried out in the United States, Toronto, Australia, Sweden, Asia, Ghana, South Africa, Somalia and even in Zimbabwe. The research questions were: How do teachers perceive the use of group work with ECE learners? What prompts ECE teachers to use group work in their classrooms? Do ECE teachers enjoy using group work with their learners? The research went on to review literature that is pertinent to teachers’ perceptions on the role of group work and it was linked to the research questions. Some teachers of children aged between six and nine agreed to having experienced positive outcomes on the part of the teachers as well as their learners with group work in their classrooms. These included learners getting to know each other better, having the opportunities to learn to interact with each other and managing their time effectively. Five schools that were involved in this project were randomly selected from a total of seven schools in the cluster. Forty ECE teachers in these five schools made the sample. The Descriptive survey research design was adopted and data was collected using the questionnaire that was self-administered to the participants. A quantitative method of data analysis was used to analyse data collected through the questionnaire while statistical data were qualitatively described. The number/percentage statistical analysis was used. The presentation of the data was done using tables, pie charts and bar graphs. These helped to illustrate data as well as for easier comprehension. The data were analysed in a bid to answer the research questions that were posed for this study. The findings of the research revealed a variety of factors and some of these are that all the teachers who participated in the research, utilised group work with ECE learners in their classrooms during teaching and learning, not all teachers enjoy using this teaching method. The ECE teachers in this study perceived that group work cannot be used in all curriculum subjects. The respondents also indicated that they assist their learners during group work. Having gathered the perceptions of ECE teachers on using group work with ECE learners, some recommendations were drawn and these included ECE teachers to enjoy teaching using group work, to be flexible when allocating learners into groups so as to provide them with the opportunities to self-select their groups as well as encourage learners who are not working cooperatively during group work to try so that they collaborate with other group members in their learning.